Public law and the UK Supreme Court : key cases and decisions - Graham, Lewis (Editor of UK Public law); Russell, Jenny (Routledge, 2026)
"This volume brings together expert commentators across different fields of Public Law to comment on a key decision by the UK Supreme Court (UKSC). Each author explores their case's content, as well as its broader implications for public law as a field and the Supreme Court as an institution. The work is divided into the following areas: Constitutional Law; Administrative Law and Judicial Review; Human Rights; and Criminal Law and Criminal Justice. Providing expert commentary on recent authorities of the highest level in one place, the collection will enable readers interested in these areas to conveniently locate analysis that will aid them in their work. Taken together, the contributions enable identification of persistent themes within subject areas. As such, it will be an invaluable resource for academics, researchers, practitioners, judges and policymakers"-- Provided by publisher.
Keywords: Public law -- Great Britain.; Public law -- Great Britain -- Cases.; Great Britain. -- Supreme Court.; Constitutional law -- Great Britain -- Cases.; Administrative law -- Great Britain -- Cases.; Judicial review -- Great Britain -- Cases.; Criminal law -- Great Britain -- Cases.; Civil rights -- Great Britain -- Cases.; elektronické knihy; electronic books